2010
DOI: 10.1007/s00429-010-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of distribution of serotonergic fibers to the thalamus of the rat

Abstract: It is well established that serotonergic (5-hydroxytryptamine, 5-HT) fibers, mainly originating from the dorsal and median raphe nuclei of the brainstem, distribute throughout the forebrain, most heavily to 'limbic' forebrain structures. Few reports have examined the distribution of 5-HT fibers to the thalamus and none to our knowledge using immunoprocedures for the detection of the serotonin transporter (SERT)-a very sensitive marker for 5-HT fibers. Using immunohistochemical methods for SERT, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 112 publications
(136 reference statements)
4
41
0
2
Order By: Relevance
“…Studies examining the 5-HT innervation of thalamus using immunostaining for 5-HT or SERT have shown that serotonergic axons are much more heavily concentrated in 'limbic' (nonspecific) than in principal (relay) nuclei of the thalamus (Cropper et al, 1984;Lavoie and Parent, 1991;Vertes et al, 2010). For instance, using antisera to SERT, we demonstrated that 5-HT fibers are densely distributed in the anterior, midline, intralaminar and mediodorsal nuclei of thalamus (Vertes et al, 2010).…”
Section: -Ht Influence On Thalamocortical Systemsmentioning
confidence: 63%
See 2 more Smart Citations
“…Studies examining the 5-HT innervation of thalamus using immunostaining for 5-HT or SERT have shown that serotonergic axons are much more heavily concentrated in 'limbic' (nonspecific) than in principal (relay) nuclei of the thalamus (Cropper et al, 1984;Lavoie and Parent, 1991;Vertes et al, 2010). For instance, using antisera to SERT, we demonstrated that 5-HT fibers are densely distributed in the anterior, midline, intralaminar and mediodorsal nuclei of thalamus (Vertes et al, 2010).…”
Section: -Ht Influence On Thalamocortical Systemsmentioning
confidence: 63%
“…Nielsen et al (2006) showed that SERT as a biomarker for 5-HT produces a stronger signal than antisera to serotonin. We found that both 5-HT and SERT immunohistochemistry produce similar patterns of serotonergic labeling, but that SERT immunostaining, by heightening signal to background, provided a bolder representation of labeled 5-HT fibers (Vertes et al, 2010).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Thalamic 5-HT projections mainly originate from the small-to-medium sized 5-HT neurons located in the DR and MR nuclei (Dahlstroem and Fuxe 1964;Vertes et al 1999). Several studies have described a dense and heterogeneous distribution of 5-HT fibers within the thalamus; serotonergic fibers are heavily concentrated in midline, intralaminar and association thalamic nuclei, and with the exception of the dLGN, they are also weakly distributed in principal thalamic nuclei (Vertes et al 2010;Rodriguez et al 2011).…”
Section: Thalamusmentioning
confidence: 99%
“…Some structures of the ventral forebrain, such as the ventral pallidum and globus pallidus also send GABAergic projections in (Churchill 1996), as does the substantia nigra pars reticulata (Tanibuchi 2009). The midline thalamus also receives serotonergic (Vertes 2010), dopaminergic (Garcia-Cabezas et al 2009) and adrenergic (Vogt et al 2008) inputs as well, indicating that midline thalamic output is regulated in a complicated manner.…”
Section: Anatomy Of the Midline Thalamusmentioning
confidence: 99%